Enfoques interaccionales en la lingüística contemporánea: ¿un posible cambio de perspectiva? - Baran, Marek (Studia Romanica Posnaniensia, 2019)
The study analyses the progressive implementation of interactional approaches in modern linguistics. Starting from the methodological assumptions of the stricto sensu conversational analysis, it is being demonstrated that the approaches initially centred on the reconstruction of the sequential model of the discourse have been opened to the perspectives, which includes not only the interactional modelling of the discursive form, but also the interpersonal construction of meaning. The article also points out the most recent fields of study of interactional linguistics, among them, the analyses dedicated to the socalled conversational negotiations, the theories of verbal politeness or the contrastive and transcultural approaches.